Factors associated with food choice values among older hemodialysis patients in selected dialysis centres in Selangor, Malaysia - Mohd Shahrin, Fatin Izzaty (2019)
Hemodialysis (HD) among the elderly has unique clinical features, where these patients have more co-morbidity, require more frequent hospitalization and use more drugs and health services compared to the younger populations. In addition, poor nutritional status may impede their appetite, food accessibility, and preparation. With individual’s social lives mainly focused around food, the foodrelated activities (e.g., shopping, cooking and dining out) become of greater significance to the elderly but are more difficult to achieve. Thus, this study aimed to determine the factors associated with food choice values (FCVs) among HD elderly in selected dialysis centres. A cross-sectional study was conducted among 119 elderly, aged 60 years and above on maintenance HD. By using simple random sampling, nine HD centres were selected from Petaling and Hulu Langat districts, Selangor as the study locations. Socio-demographic, dietary intake, malnutrition risk, depression, health-related quality of life (HRQOL) and FCVs were assessed via interview session. Dialysis Malnutrition Score (DMS) was used to evaluate nutritional status while Patient Health Questionnaire-9 (PHQ-9) used to assess the severity of depressive symptoms. HRQOL was assessed by using the Kidney Disease Quality of Life-36 (KDQOL-36) questionnaire. The medical profile and dry weight were obtained from the subjects' medical records. Anthropometric assessments such as height, pre-dialysis weight, and post-dialysis weight were also conducted. The variables associated with FCVs were tested with Pearson Correlation and Multiple Linear Regression (MLR). The mean age of the subjects was 67±6 years. The subjects comprised of approximately equal number of males (50.4%) and females (49.6%). Majority of the subjects were Malay (60.5%). Hypertension (87.4%) and diabetes mellitus (71.4%) were the major co-morbidities among subjects. There were 49.6% of the subjects who did not achieve the desirable serum albumin of ≥40 g/L, 58.0% had high serum phosphate (>1.6 mmol/L) while 61.3% of the subjects had low hemoglobin level. About 6.7% of the subjects were underweight. Majority of the subjects had inadequate energy and protein intakes (91.6%), were moderately malnourished (71.4%), non-depressed (84.0%) and obtained better HRQOL score in terms of symptoms/problems (73.37±17.01) and effects of kidney disease (72.63±19.74) subscales. Safety, sensory appeal, and organic factors were the strongest perceived of FCVs. There was a significant negative correlation between age (p<0.05), energy intake (p<0.05), protein intake (p<0.01) and fat intake (p<0.01) with total FCVs score. The MLR model suggested that 12.1% of the variance in the FCVs was explained by age and fat intake. In conclusion, this research found that health was not the main factor in determining the FCVs among HD elderly. Instead, safety, sensory appeal, and organic factors were deemed to be more important when assessed by FCVs questionnaire. Subject who experienced aging and increased in total energy, protein and fat intakes felt that food choice was no longer important. Age and fat intake also had an impact on FCVs of HD elderly. Thus, these findings could be taken into account for dietitians to understand the factors associated with FCVs when designing and delivering nutritional intervention regarding healthy choices of fat intake targeting HD elderly.